How Does Climate Change Affect the Transition of Power Systems: The Case of Germany - Alexander Golub; Kristina Govorukha; Philip Mayer; Dirk Rübbelke (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The effects of extreme weather events, such as heat waves and droughts, are taken into account in both global and European policies. Accordingly, the protection of critical infrastructures and in particular, the resilience of the energy sector was the subject of intense research. There are regional differences in the degree to which extreme events affect the energy sector. In Northern Europe, their intensity has increased dramatically within a decade. In our analysis, we identify emerging risks of extreme weather events, in particular, droughts and high temperatures, for the German power sector. Our analysis is based on extensive datasets comprising temperature and drought data for the last 40 years. We find evidence of a higher frequency of power plants outages as a consequence of droughts and high temperatures. We investigate increases in the wholesale electricity price and price volatility and develop a capacity-adjusted drought index. The results are used to assess the monetary loss of power plant outages due to heat waves and droughts. We stress that increasing frequencies of such extreme weather events will aggravate the observed problem, especially with respect to the transition of the power sector.
Keywords: Q40; Q41; Q54; 330; electricity; utilities; thermal generation; climate change; droughts; weather extremes